Economic, environmental, and social assessment of bioethanol production using multiple coffee crop residues. (1st February 2021) - Duarte, Alexandra; Uribe, Juan Carlos; Sarache, William; Calderón, Andrés
Abstract: The use of agricultural residues for bioethanol production greatly depends on availability of raw materials and the proper design of a flexible multi-feedstock facility. Therefore, this article assesses the economic, environmental, and social feasibility of a bioethanol production plant, using multiple coffee crops residues (stems, pulp, and mucilage). A case study was designed for the Colombian context, considering three scenarios for different capacity plant. Results suggest that the production costs of 0.504, 0.508, and 0.515 $USD/l for large, medium and small capacity, respectively, are comparable to the bioethanol market price and are similar to other studies reported in the literature. The CO2 emissions obtained were 1.296 Kg CO2 /l, 1.297 Kg CO2 /l and 1.3 Kg CO2 /l for the large, medium, and small plants respectively. The large plant requires 1, 170 million tons per year of fresh water, and generates a gray water footprint of 119 thousand tons per year. However, without recirculation, 2.87 times more water is required. Favorable results were identified in terms of reduction of collateral environmental effects, as well as positive impacts on social aspects. Finally, a sensitivity analysis shows the impacts of key parameters on economic, social, and environmental merits of producing bioethanol from coffee residues. Highlights: A multipurpose bioethanol plant using multiple coffee residues is analyzed. Coffee stems, pulp, and mucilage were used as raw materials. Technical, economic, environmental, and social aspects were considered. The results demonstrate the feasibility of coffee residues for bioethanol production.